A comparison between the time of the Belgic confession and the Korean Church (with reference to martyrdom and persecution) - Van der Merwe, J.M. (Johan Matthys) (University of Pretoria, 2013)
Dissertation (MA(Theol))--University of Pretoria, 2011.